Front Cover: A Modular Ligation Strategy for Asymmetric Bivalent Nucleosomes Trimethylated at K36 and K27 (ChemBioChem 9/2019). (10th April 2019) - Guidotti, Nora; Lechner, Carolin C.; Bachmann, Andreas L.; Fierz, Beat
Abstract : The front cover picture shows the assembly of asymmetric nucleosomes, trimethylated at lysine 27 (K27) on one H3 molecule and at K36 on the other, which are observed at promoters of developmental genes in embryonic stem cells. Efficient and modular assembly instructions for such nucleosomes are given in the communication by N. Guidotti, B. Fierz et al. on page 1124 in Issue 9, 2019 (DOI: 10.1002/cbic.201800744 ). The strategy relies on a three‐segment ligation coupled with a protease‐cleavable peptide tag, "lnc‐tag". This tag forces two differently modified H3 molecules into the same nucleosome and ensures the generation of defined combinatorial histone modification patterns. Using this assembly strategy, the authors show that trimethylation of K36 hinders PRC2 activity while prolonging its residence time on modified chromatin fibers.